Application of Copper Increased Corn Yield through Enhancing Physiological Functions - Mohd. Hudzari, Haji Razali; Mohammad Moneruzzaman, Khandaker; Nashriyah, Mat (2014)
Copper (Cu) is needed by the corn plant in small amount and play an active role in plant metabolism. In order to evaluate the effects of copper on corn production, an experiment was conducted in the field. In this study, the effects of Cu on corn production were studied with regard to plant parameters, relative water content (RWC), chlorophyll (Chl) content, chlorophyll (Chl) fluorescence, photosynthesis parameters, and yield parameters. Different Cu concentrations (0, 0.2, 1.5 and 3 ppm) were applied as a foliar spray on leavesof corn plants. Plants’ height wasinduced by the application of different Cu applications (1.5 and 3 ppm) but not on leaf numbers. Relative water content (RWC) increased gradually with increasing Cu concentration. On the other hand, net photosynthesis rate (Pn) and photosynthetically active radiation (PAR)decreased with increasing Cu concentration. Chlorophyll (Chl) content increased in leaves of Cu-treated plants than Cu-untreated plants andChl fluorescence data showed similar to Chl content data.Cu application increased yield compared than control but higher Cu concentration showed better results. Taken together, it seems that Cu at 1.5 ppm as foliar applicationshowed better result in terms of increasing production and improving physiological function of corn plants.